2006
DOI: 10.1175/jcli3801.1
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrated Seasonal Forecasting System for South America

Abstract: This study proposes an objective integrated seasonal forecasting system for producing well-calibrated probabilistic rainfall forecasts for South America. The proposed system has two components: (i) an empirical model that uses Pacific and Atlantic sea surface temperature anomalies as predictors for rainfall and (ii) a multimodel system composed of three European coupled ocean-atmosphere models. Three-month lead austral summer rainfall predictions produced by the components of the system are integrated (i.e., c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 37 publications
2
59
0
3
Order By: Relevance
“…This is especially true when combined with methods that can provide forecasts for the large-scale aspect of monsoons, such as statistical methods (e.g., Moron et al, 2009a,b;Stolbova et al, 2016), dynamic prediction of monsoon indexes (e.g., Vellinga et al, 2013;Alessandri et al, 2015), and even the integration of statistical and dynamical prediction (e.g., Coelho et al, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This is especially true when combined with methods that can provide forecasts for the large-scale aspect of monsoons, such as statistical methods (e.g., Moron et al, 2009a,b;Stolbova et al, 2016), dynamic prediction of monsoon indexes (e.g., Vellinga et al, 2013;Alessandri et al, 2015), and even the integration of statistical and dynamical prediction (e.g., Coelho et al, 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recent studies for target regions have shown that a careful post-processing (Coelho et al, 2006) and combination of information from different forecast systems, including statisticalempirical schemes (Stephenson et al, 2005), and predictor's expertise (Schubert et al, 2007) can significantly increase the forecast quality of seasonal predictions. This is certainly possible in our case, since the three forecast systems described here possess complementary strengths in their abilities to sample structural, parameter and initial-condition uncertainties.…”
Section: F J Doblas-reyes Et Almentioning
confidence: 99%
“…Notwithstanding this progress, the north-eastern interior remains an area where SSTs are producing high forecast skill, although the GCM and GCM-MOS systems also produce high skill there. It should be worthwhile to investigate whether or not a combination of physical model output and statistical forecast models that use SSTs as predictors can further improve skill (Coelho et al, 2006) over South Africa.…”
Section: Discussionmentioning
confidence: 99%